Understanding the logics of pheromone processing in the honeybee brain: from labeled-lines to across-fiber patterns - Sandoz, Jean-Christophe; Deisig, Nina; De Brito Sanchez, Maria Gabriela; Giurfa, Martin (Frontiers in Behavioral Neuroscience, 2007)
Honeybees employ a very rich repertoire of pheromones to ensure intraspecific communication in a wide range of behavioral contexts. This communication can be complex, since the same compounds can have a variety of physiological and behavioral effects depending on the receiver. Honeybees constitute an ideal model to study the neurobiological basis of pheromonal processing, as they are already one of the most infl uential animal models for the study of general odor processing and learning at behavioral, cellular and molecular levels. Accordingly, the anatomy of the bee brain is well characterized and electro- and opto-physiological recording techniques at different stages of the olfactory circuit are possible in the laboratory. Here we review pheromone communication in honeybees and analyze the different stages of olfactory processing in the honeybee brain, focusing on available data on pheromone detection, processing and representation at these different stages. In particular, we argue that the traditional distinction between labeled-line and across-fi ber pattern processing, attributed to pheromone and general odors respectively, may not be so clear in the case of honeybees, especially for social-pheromones. We propose new research avenues for stimulating future work in this area.